Whole-exome sequencing in Saudi colorectal cancer patients reveals distinct mutational patterns and population specific pathogenic variants - Alatwi, Hanan E.; Alharbi, Amnah A.; Mir, Rashid; Alzahrani, Othman R.; Alessa, Abdulrahman H.; Hawsawi, Yousef M.; Arishi, Mohammed Ali; Albalawi, Aziz Dhaher (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) shows significant inter-population heterogeneity in its genomic landscape, yet Middle Eastern populations are underrepresented in large-scale sequencing studies. This exploratory study aims to characterize somatic mutations and disrupted signaling pathways in Saudi Arabian CRC patients.MethodsWe performed whole-exome sequencing (WES) on tumor DNA from 24 Saudi CRC patients. Somatic variants were identified and analyzed in a curated panel of cancer-related genes. Comparative analysis was conducted against The Cancer Genome Atlas colorectal cancer dataset (TCGA-COADREAD), and pathway enrichment analysis was performed.ResultsSomatic variants were identified in 23 tumors, with recurrent mutations in BRCA2 (61%), TCF7L2 (52%), EGFR (43%), and SOS1 (43%). Compared to TCGA-COADREAD, mutation frequencies were significantly higher in BRCA2, EGFR, SLC25A5, and PIK3R2 (adjusted p < 0.0001). Among 258 total variants, 43% were novel, and 25 were classified as pathogenic, likely pathogenic, or deleterious, including 13 novel variants across nine genes. Pathway analysis revealed frequent disruptions in WNT/β-catenin (65%), homologous recombination (61%), PI3K (48%), and RTK/RAS (43%) signaling pathways.ConclusionOur results reveal a distinct mutational profile in Saudi CRC patients, characterized by novel and enriched somatic variants affecting key oncogenic pathways. These findings underscore the necessity of including underrepresented populations in cancer genomics to support globally equitable precision oncology.